Combining ability for some salinity tolerance traits in rice (Bangladesh Journal of Agricultural Research, 2007)
Eight parents and 28 F1s excluding reciprocals were tested for three salinity tolerance traits viz., Na+ concentration, Na/K ratio and visual score at EC 9.0-9.5 dS/m to know the genetic information and the nature of combining ability of the parents and their performances in F1 hybrids. Mean values of F1s for shoot Na+, Na/K ratio, and visual score were lower compared to parents indicated dominance of tolerance. Significant GCA and SCA effects in all the traits suggest the importance of both additive and non-additive gene actions. Much higher GCA effects than SCA effects indicated preponderance of additive gene action for salinity tolerance. Pokkali, Nonabokra, and Binnatoa were the good general combiners. Most of the best crosses were obtained from susceptible parents crossed with tolerant parents. Transfer of salinity tolerant traits from these varieties to modern varieties may offer potential for increasing the level of salinity tolerance in rice. Bangladesh J. Agril. Res. 32(2) 2007: 183-189.